Navigating transfusion challenges: Bombay blood group in focus - Romesh Jain; Vilasini Patil; Pratul Sinha; Snehashish Mishra; Rut Naik (Journal of Education and Health Promotion)
“Bombay” and “Para-Bombay” phenotypes are uncommon blood groups with absence or deficiency of H antigen. These individuals possess anti-H antibodies and crossmatching with ABO blood group packed red blood cells (PRBC) becomes incompatible. In this report, we find out alternative strategy (patient blood management) for the management of anemia in Bombay blood group patient. Case: A 49-year-old woman referred to our hospital with severe anemia (Hb = 6 gm/dl). On history patient visited to peripheral hospital with complains of fatigue and weakness. Patient was transfused one unit of group O PRBC and suffered hemolytic transfusion reaction. At our center, blood group analysis was performed by the standard tube technique. In the forward group, there was negative reaction with anti-A, anti-B, and anti-AB sera, and 4+ reaction was showing with anti-D sera. In reverse grouping, there was 4 + reaction with A cell, B cell, and O cell and negative reaction with autocontrol. This suggests that patient was having a strong antibody other than anti-A and anti-B, which was reacting strongly with O cell at all temperatures. Anti-H lectin reaction was negative. The patient was diagnosed with probable Bombay phenotype (hh), and we tried to manage anemia with patient blood management. Patient was started on oral iron supplementation, and after 2 month of treatment, the patient had Hb of 13.3 gm/dl with no complains of fatigue and weakness. In this report, we reiterate the importance of patient blood management and would also like to emphasize to implement the rare group registry in India.